Uma “Guerra” Santa de Ideias nas obras de Ramon Llull (1232-1316): as estratégias de evangelização e conversão dos não-cristãos - MATEUS, Natasha Nickolly Alhadef Sampaio (2024)
This thesis aims to analyze the strategies of evangelization and conversion of the so-called “infidels” to Christianity, as a “Holy War of Ideas”, through the speech of the philosopher Ramon Llull contained in his books Doctrine for The Book of the Gentile (1274-1276). and the Three Wise Men (1274-1276). As a theoretical foundation, research is used that deals with Social History, Hebe Castro (2011) and the History of the Imaginary, Le Goff (2006) and Global History, Crosley (2014) and Conrad (2019).The methodology of this research is bibliographic, comparative and Critical Discourse Analysis. The problem of this doctoral research is: what are the means used by Ramon Llull in the process of converting non-Christians in the face of a global project to expand Christianity? The guiding hypothesis of this research points out that the books, Doctrine for children and The Book of the Gentile and the Three Wise Men (1274-1276), by Ramon Llull were ambitious and comprehensive beyond what is imagined regarding religiosity, but wanted unification of Christianity. The author discursively instrumentalized the Christian message as a strategy of cultural resistance against the muslim empire in the Iberian Peninsula and other locations. It is important to highlight that the Majorcan offers in his speech formative and also theological elements of this Christian that he intends to constitute for combat, that is, for a “Holy War of Ideas”, with the intention of proving the veracity of the Christian faith, training missionaries for the spread and expansion of the Catholic faith in the territories “reconquered” by Christians in the Iberian Peninsula and beyond. This research seeks to show that the dispute for the maintenance of Christianity in Christian discourse influenced several intellectuals such as Ramon Llull, who placed themselves at the service of this institution in propagating the ideas of life in the afterlife, but also earthly conquest.